Uji Kinerja Oven Pengering Spesimen Cat Tipe Tertutup Dengan Penambahan Isolator Aluminium Foil - Hadiputranto, Rachmanto; Andriansah, Acep Hendra; Rizki, Aldi Mochamad (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2024)
This research is a development study on the design of a laboratory scale paint specimen drying oven with a 100 Watt incandescent lamp heat source. This research focuses on the impact of adding aluminum foil insulators on the overall interior of the oven. The aim of the research is to determine the performance of the oven with the main indicators including the maximum temperature that can be achieved, the time required to reach the maximum temperature and the thermal efficiency of the oven. The research method used is testing by applying the principles of the First Law of Thermodynamics regarding Conservation of Energy. Tests were carried out in 11 varying temperature conditions, starting from room temperature of 300 Kelvin. From the test, input data is obtained in the form of electric current, voltage and electric power. Input data includes temperature, heating time and power required to heat the oven chamber. Two input and output data are used to calculate the thermal efficiency of the oven. The final test results were compared with the performance of the oven without an isolator and there was a change in performance. The final results of the research showed that the addition of the aluminum foil insulator was able to increase the maximum temperature of the oven to 330.13 K from 327.57 K before without the insulator. The heating time with the aluminum foil insulator was faster to 2785.6 seconds compared to 3150.56 seconds before without the insulator. . The average thermal efficiency with an aluminum foil insulator is 90.93% from 94.50% without an insulator. Key words:, Aluminum Foil, Insulator, Closed Oven